2023
DOI: 10.3390/ma16020668
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Performance of Coated Carbide Tool during Dry Turning of AISI 4340 Alloy Steel

Abstract: The machinability of materials is highly affected by their hardness, and it affects power consumption, cutting tool life as well as surface quality while machining the component. This work deals with machining of annealed AISI 4340 alloy steel using a coated carbide tool under a dry environment. The microhardness of annealed and non-annealed workpieces was compared and a significant reduction was found in the microhardness of annealed samples. Microstructure examination of the annealed sample revealed the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 49 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…40CrNi2MoE steel, belonging to the nickel–chromium–molybdenum series of low-alloy ultra-high-strength steels, epitomizes exemplary material characteristics, including notable strength, toughness, and favorable hardenability. As a result, its usage spans a wide range of applications, prominently in the manufacture of vital components like aircraft landing gears [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…40CrNi2MoE steel, belonging to the nickel–chromium–molybdenum series of low-alloy ultra-high-strength steels, epitomizes exemplary material characteristics, including notable strength, toughness, and favorable hardenability. As a result, its usage spans a wide range of applications, prominently in the manufacture of vital components like aircraft landing gears [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous factors related to machining fluids, including pressure, application technique, cutting fluid flow rate, impact tool [16-,17]. Wagri et al, [19], the surface integrity of hardened AISI 4140 steel was studied while being turned using a scalable pulsed power plasma SPPP-AlTiSiN coated carbide tool with minimal quantity lubrication (MQL) assistance from nanofluids. Radiator coolant and zinc oxide nanoparticles are combined to create nano-cutting fluid.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it projected the entire machining cost per component to be Rs.23.12 in Indian rupees. In the study carried out by Wagri et al [19], it was confirmed that the hardness of a material significantly impacts its machinability, which in turn impacts the component's surface quality, power consumption, and cutting tool life [20]. However, the current machining fluid employed in the industry, e.g., soluble oil, is not environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%
“…Cooling of the machining zone is of paramount importance to address the problems caused by excessive heat. Many studies have been conducted to optimize cutting parameters of AISI 4340 alloy steel and improve the quality of the machined surface [3][4][5][6]. In these studies, researchers have focused on reducing surface roughness to ensure the integrity of the machined surface, minimizing tool wear and the resulting increase in cutting forces, reducing power consumption, enhancing machining efficiency, optimizing cutting parameters such as cutting speed and feed rate, as well as controlling pa-rameters such as cooling and lubrication methods, and exploring environmentally friendly green manufacturing [7].…”
Section: Introductionmentioning
confidence: 99%